A characteristic method for porous medium flow. (8th January 2008) - Al-Lawatia, Mohamed; Wang, Kaixin; Telyakovskiy, Aleksey S.; Wang, Hong
We present an efficient and accurate characteristic method for the solution of the unsteady-state advection-diffusion transport equations, which arise in the mathematical models for flow and transport processes in porous media. The advantages of this method include symmetrising the governing transport equation, treating boundary conditions naturally in the formulation, and conserving mass. Moreover, because of the Lagrangian nature of the algorithm used, the method generates accurate numerical solutions even when large time steps and coarse spatial grids are used in the simulation. Numerical experiments are presented to illustrate the performance of the method.